2014
DOI: 10.1016/j.alcohol.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory spatial profile of alcohol's effects on the resting state: Anatomically-constrained MEG

Abstract: It has been firmly established that opening and closing the eyes strongly modulate the electro- and magnetoencephalography (EEG and MEG) signals acquired during wakeful rest. Certain features of the resting EEG are altered in chronic alcoholics and their offspring, and have been proposed as biomarkers for alcoholism. Spontaneous brain oscillations are also affected by pharmacological manipulations, but the spectral and spatial characteristics of these changes are not clear. This study examined effects of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 108 publications
4
14
0
Order By: Relevance
“…Thus, the decrease in alpha band in occipital areas of the BD group may be related to a deficit in memory compatible with cognitive studies with this population showing deficits in memory tasks 21,22,75 . Besides, a recent study has shown that acute alcohol intoxication also affects alpha band, increasing its short-term power mainly during eye-closed resting state, also measured by MEG 76 . Therefore, it would be possible that a pattern of consumption that includes repeated alcohol intoxication, as BD, affects long-term PS and, specifically to alpha power.…”
Section: Ps Differencesmentioning
confidence: 99%
“…Thus, the decrease in alpha band in occipital areas of the BD group may be related to a deficit in memory compatible with cognitive studies with this population showing deficits in memory tasks 21,22,75 . Besides, a recent study has shown that acute alcohol intoxication also affects alpha band, increasing its short-term power mainly during eye-closed resting state, also measured by MEG 76 . Therefore, it would be possible that a pattern of consumption that includes repeated alcohol intoxication, as BD, affects long-term PS and, specifically to alpha power.…”
Section: Ps Differencesmentioning
confidence: 99%
“…Acute alcohol intoxication induces a decrease in alpha oscillatory frequency and an increase in alpha power (Ehlers, Wall, & Schuckit, 1989; Nikulin, Nikulina, Yamashita, Rossi, & Kahkonen, 2005). Source modeling of the MEG signal has confirmed that alpha power is generated primarily in the medial parieto-occipital area and is increased during alcohol challenge (Rosen et al, 2014). Studies of rsEEG reveal lower alpha power in individuals with alcohol use disorder (AUD) (Begleiter & Platz, 1972; Saletu-Zyhlarz et al, 2004) who also exhibit a low-voltage alpha (LVA) variant that is comorbid with high anxiety (Enoch & Goldman, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Electro- and magnetoencephalography (EEG and MEG) are used to measure spontaneous neural oscillations during wakeful rest, also termed resting-state, rsEEG/MEG (Rosen et al, 2014; Schomer & Lopes da Silva, 2011). Because it does not require any task engagement, this method has been applied across ages and in diverse populations to examine spontaneous oscillations in various brain-based disorders and conditions (Porjesz et al, 2005; Schomer & Lopes da Silva, 2011) including chronic alcoholism (Begleiter & Porjesz, 2006; Porjesz et al, 2005; Rangaswamy & Porjesz, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, simultaneous EEG recordings showed no differences, suggesting that MEG had superior sensitivity than EEG. Similarly, Rosen et al (2014) showed that alcohol (0.6 g/kg men/0.55 g/kg women, oral) strongly increased alpha power in eyes-closed conditions with minimum norm source estimates, identifying sources in the medial occipitoparietal area. Small increases in theta and beta were also seen with alcohol localised to the anterior cingulate cortex.…”
Section: Alcoholmentioning
confidence: 94%